Abnormal hubs in global network as potential neuroimaging marker in generalized anxiety disorder at rest - Meng, Lili; Zhang, Yuandong; Lin, Hang; Mu, Jingping; Liao, Heng; Wang, Runlan; Jiao, Shufen; Ma, Zilong; Miao, Zhuangzhuang; Jiang, Wei; Wang, Xi (Frontiers in Psychology, 2022)
Abstract Background: Mounting studies have reported altered neuroimaging features in generalized anxiety disorder (GAD). However, little is known about changes in degree centrality (DC) as an effective diagnostic method for GAD. Therefore, we aimed to explore the abnormality of DCs and whether these features can be used in the diagnosis of GAD. Methods: Forty-one GAD patients and 45 healthy controls participated in the study. Imaging data were analyzed using DC and receiver operating characteristic (ROC) methods. Results: Compared with the control group, increased DC values in bilateral cerebellum and left middle temporal gyrus (MTG), and decreased DC values in the left medial frontal orbital gyrus (MFOG), fusiform gyrus (FG), and bilateral posterior cingulate cortex (PCC). The ROC results showed that the DC value of the left MTG could serve as a potential biomarker with high sensitivity and specificity for distinguishing patients from healthy controls. Conclusions: Our findings demonstrate that abnormal DCs in the left MTG can be observed in GAD, highlighting the importance of GAD pathophysiology.